Satire, Identity, and Social Hypocrisy in the Importance of Being Earnest - Vania Putri Filindity; Maria Riska Fantika (TEKILA: Journal of Language Teaching and Literature, 2026)
This study aims to critically analyze character development and conflict in Oscar Wilde’s play The Importance of Being Earnest (1895). Using a qualitative descriptive approach, the analysis focuses on the main characters, the structure of conflict, and the thematic messages conveyed in the play. The findings reveal that the characters, particularly Jack Worthing and Algernon Moncrieff, construct false identities to escape social responsibilities, reflecting the theme of deception and the fluid nature of identity. The central conflict arises from misunderstandings and the use of fabricated identities, which develop through comedic situations and are ultimately resolved through the revelation of truth. The play also highlights themes of social hypocrisy, class consciousness, and the superficial nature of Victorian values, especially in relation to love and marriage. Through satire and witty dialogue, Wilde critiques a society that prioritizes appearance over sincerity and moral integrity. Although the play demonstrates strong use of humor and consistent characterization, it presents limited character development due to its reliance on static characters typical of comedic drama. Overall, The Importance of Being Earnest serves as a significant literary work that exposes social conventions while entertaining audiences, making it relevant for both literary and cultural analysis.